Shoreline Changes for 20 Years (2001-2021) and 2041 Predictions and Adaptation of Coastal Communities - Amalia, Febrianti; Zairion, Zairion; Atmadipoera, Agus Saleh (JST (Jurnal Sains dan Teknologi), 2023)
Shoreline alteration in Semarang continues to increase, causing abrasion, accretion, and tidal flooding yearly. Coastal damage has resulted in significant ecosystems in coastal areas losing their role in maintaining the stability of the coastline during the last two decades. This study aimed to analyse shoreline alterations from 2001 to 2021 and predict shoreline alterations over the following 20 years, together with alternative coastal community adaptations. The analytical method employed DSAS 5.0 with an End Point Rate statistical approach for shoreline alterations; on the other hand, Linear Regression Rate analysis was utilised for 2041. Concerning coastal community adaptation, specifically through interviews. The study’s findings indicated that Semarang City experienced abrasion of approximately 10,31 m/year and accretion of approximately 20,95 m/year between 2001 and 2021. Abrasion and accretion will be slightly lower in 2041, at around 10,15 m/year and 19,69 m/year, respectively. The Protective and Accommodative Strategy is the proposed adaptation strategy for future changes.